Conflicting Logics, Mechanisms of Diffusion, and Multilevel Dynamics in Emerging Institutional Fields - Purdy, Jill M.; Gray, Barbara (Academy of Management Journal, 2009)
We examine the evolution of a new population of organizations (state offices of dispute resolution) in an emerging institutional field, focusing on how actions at multiple levels interact recursively to enable multiple logics to diffuse. Logics became institutionalized as organizational practices within the field of alternative dispute resolution through four diffusion mechanisms: transformation, grafting, bridging, and exit. By describing the interplay among entrepreneurial efforts, strategic responses to resource dependencies, and mechanisms of institutionalization over 22 years, we identify the conditions that enabled multiple practices supported by conflicting logics, rather than a single, dominant organizational form, to be institutionalized.